Factors Related to the Incidence of Malaria in Konawe Islands Regency - Orin, Orin; Saafi, La Ode; Azizi Jaya Jayadipraja, Erwin (Magister Kesehatan Universitas Mandala Waluya, 2023)
Introduction: This study aims to analyze risk factors related to the incidence of malaria in Konawe Islands Regency. Methods: Research used in this study is observational research with case control design. Case groups are all respondents who have been affected by malaria, while the control group is a person who is negatively plasmodium. This study was conducted in Konawe Islands Regency with a sample of 92 respondents, consisting of 64 case groups and 46 control groups in Konawe Islands Regency. Results: Bivariate analysis which is a risk factor for malaria events is the environmental factor of the ceiling (p-value = 0.028 OR = 3,500 Cl 95%= 1,112-11,017) and puddles (p-value = 0.037 OR = 3,763 Cl 95%= 1,038 - 13,646) Conclusion: From the results of multivariate analysis, risk factors that affect malaria events are the existence of breeding sites, the condition of the walls of the house and the presence of bushes. The most influential factor on the risk of malaria events is the presence of breeding site (P-value = 0.028 OR = 3,500 Cl 95%= 1,